Prolactin – friendly lactation hormone or hostile cancerogenic factor? - Leziak, Milena; Niedobylski, Sylwiusz; Żak, Klaudia; Skórzyńska-Dziduszko, Katarzyna; Krasowska, Danuta (Journal of Education, Health and Sport, 2019)
Prolactin is a hormone secreted by lactotrophic cells of the pituitary gland and its main function is stimulating lactation. Binding prolactin by its membrane receptor leads to the activation of signalling pathway that enables cell proliferation and differentiation. Due to this mechanism, the potential oncogenic role of the hormone is of great interest. Prolactin and its receptor have many forms and a complicated signalling pathway, that is why defining prolactin’s specific role in cancerogenesis is difficult and poses a serious challenge. Researches also indicate an important role of extra-pituitary prolactin synthesised in many other tissues in the process of cancerogenesis. This article focuses on connection between prolactin and breast cancer, as it is the most common cancer in women. In several studies, prolactin and its receptor were significantly associated with an increased breast cancer risk. Recent research papers focus also on the treatment of breast cancer, using knowledge about prolactin and its role in the development of the tumour.